Modern contraceptive practices and associated predictors among married women: a cross-sectional study at tertiary care centre in Jharkhand - Narain, Smiti; Kiran, Asha; Kujur, Manisha; Trivedi, Kiran; Kujur, Anit (International Journal of Research in Medical Sciences, 2023)
Background: World Health Organization defines family planning as a way of thinking and living that is adopted voluntarily, upon the basis of knowledge, attitudes and responsible decisions by individuals and couples, in order to promote the health and welfare of the family group and thus contribute effectively to the social development of a country. The objectives of the study were to estimate contraceptive usage in married females of the reproductive age group and its determinants. Methods: A cross-sectional analytical study was conducted in Obstetrics and Gynecology Department, RIMS, Ranchi. Study participants were married females of the reproductive age group attending OPD in the study period. The sample size was calculated using scientific formula. Data collection used a pretested semi-structured questionnaire including basic information like sociodemographic profile etc. The data was analyzed using SPSS version 20. Results: The study included 384 participants. Only 20.3% of participants used one or other contraceptive methods. 68.2% had knowledge of any contraceptive method, 45.3% felt the need to use contraception and 20.3% used any particular method. Conclusions: Contraception prevalence rate varies with the socio-demographic variables in different states in India. Other indices such as couple protection rate, couple years of protection, unmet needs for family planning, etc play a vital role in determining the exact situation as compared to relying on a single indicator. An estimation of persisting KAP gap is essential before addressing the key factors of unmet needs, family planning effort indices, and contraceptive continuation rate to make community programs more efficient.